Impact of timely dialysis on mortality in patients needing emergency hemodialysis / Norfariza Abd Rahim - Norfariza, Abd Rahim (2017)
BACKGROUND: It is intuitive that in patients with clear indication for urgent hemodialysis (HD), earlier dialysis may have better outcomes. Renal Unit University Malaya Medical Centre (UMMC) bad developed a quality assurance initiative for urgent HD, whereby initiation of urgent HD is within 120 minutes after decision made. We therefore compared timely and delayed initiation of HD with mortality rate and factors contributing to it. OBJECTIVES: Our primary aim is to examine mortality rate in patients requiring urgent HD on admission. We also aim to determine factors contributing to mortality among these patients. METHODS: This is a retrospective cohort study using data obtained from Urgent HD Census from Renal Unit UMMC for 24 months between ls1 January 2015 and 31st December 2016. Patients were classified into t1mely group, if HD initiation was within 120 minutes after decision to dialyze made and into delayed group, if it was more than 120 minutes. The primary end-point was all-cause inpatient mortality comparing the 2 groups. Factors contributing to mortality among patients requiring urgent HD on admission were examined. RESULTS: Data from 415 patients were analyzed, with mean age of 60± 13 years old were included. The average time from decision to dialysis was 75 minutes in patients with timely initiation group and 227 minutes in delayed initiation group. The median time from decision to dialysis was 120 minutes. Overall mortality rate for patients needing urgent dialysis is 12.8%. Cox survival analysis showed no difference in in-patient mortality between timely initiation and delayed initiation (adjusted HR for delayed group, 0.90 (0.51-1.61 ]). Median hospitalization days for patients in timely initiation was 4 days and in delayed initiation was 5 days (p=0.03). There was significantly higher likelihood of death in patients aged 60 and above (HR 2.14 [ 1.15- 3.99], p-value 0.017). CONCLUSION: Performing dialysis within 120 minutes after decisions made does not seem to reduce in-patient mortality and does not affect the length of stay in patients requiring urgent HD. Age is the only significant predictor for mortality in this study. In addition, we need to adjust the potential confounders in this study such as to determine medical diagnosis of patients upon admission and to evaluate time of admission to time of HD among these patients to prevent bias that can distort the result in this study.